Avaliação da formação de trialometanos considerando o uso de cloro e permanganato de potássio como pré-oxidantes em águas de abastecimento - Agrizzi, Alexandre Demo (2011)
Chlorine has been used as the main pre-oxidation of organic matter, inactivating pathogenic microorganisms that live in fresh water for over one hundred years. The organic matter found in surface waters containing humic substances that can react with chlorine, generating potentially carcinogenic halogenated organic compounds, especially trihalomethanes. The main trihalomethanes that are formed are chloroform, bromodichloromethane, bromoform and the dibromochloromethane, and the sum of the concentrations of these four products is called total trihalomethanes. In water treatment plants (WTP), the stage of pre-oxidation with chlorine significantly contributes to the formation of these compounds. This research aimed to evaluate the formation of trihalomethanes after conventional treatment of water from the simulation of four different routes in bench tests (Jar-test), and specimens removed from the water treatment plants in the study. The trihalomethanes were quantified by gas chromatography with electron capture detector. Samples were collected from raw water from two springs of the state of Espirito Santo (Jucu and Sahy River), with different color, absorbance at 254 nm and turbidity. Two Oxidants were tested in analyses: chlorine (as calcium hypochlorite) and potassium permanganate. The results showed that the formation of trihalomethanes was lower when the water samples were treated with potassium permanganate in the pre-oxidation, when compared with samples treated with chlorine. A similar result occurred in the potential for trihalomethane formation for 24 hours. In relation to the potencial formation of seven days, both springs were shown to be capable of forming compounds precursors of trihalomethanes. Concentrations of trihalomethanes above the limit allowed by the Ordinance of Ministry of Health number 518 were only detected in samples of treated water from the Sahy River